Understanding Pilgrim Satisfaction: The Role of Customer Experience and Bonus Pack in Umrah Travel - Nugraha, Aa Willy; Ismail, Shafinar (Universitas Muhammadiyah Surakarta, 2025)
In the context of increasing demand for religious tourism, understanding the factors that drive satisfaction among Umrah pilgrims is essential. This study examines the impact of customer experience and bonus packs on the satisfaction of Umrah pilgrims in Indonesia. Employing a quantitative approach, data were collected from 120 respondents using a structured questionnaire and analyzed using Structural Equation Modelling with Partial Least Squares (SEM-PLS). The results reveal that both customer experience and bonus pack significantly influence satisfaction, with both factors having a partial and simultaneous impact on satisfaction. Bonus packs—comprising additional services or amenities—emerged as a strong predictor of satisfaction by enhancing perceived value during the pilgrimage journey (path coefficient = 0.376, p < 0.001). Customer experience also demonstrated a significant positive effect (path coefficient = 0.354, p < 0.038), underscoring the importance of service quality and emotional connection throughout the pilgrimage process. Simultaneously, the two constructs explain 51,5% of the variance in satisfaction (R² = 0.515). These findings underscore the strategic importance of integrating meaningful customer experiences with value-added offerings to enhance service satisfaction in Umrah travel services. Travel agencies are advised to invest in enhancing service touchpoints and bundling attractive bonus features to improve customer satisfaction. Limitations of this study include its regional focus on Tasikmalaya, which may limit its broader applicability. Future research is encouraged to include more diverse populations and investigate moderating variables such as religiosity, service innovation, and digital engagement.